PWE-006 How often is Bowel Cancer Detected from a Positive 3RD Kit in the English Bcsp?. (4th June 2013) - Field, A; Vogler, M; Logan, R F
Abstract : Introduction: In the English Bowel Cancer Screening Programme (BCSP) subjects returning a weak positive kit (1–4 of the 6 windows positive) are invited to do a 2 nd kit and if none of the windows are positive they are invited to complete a 3 rd kit. If any windows are then positive subjects are referred for possible investigation; if no windows are positive subjects are discharged from that screening round. This testing algorithm has been criticised for making the screening process too prolonged thereby producing anxiety and drop-outs and the Scottish BCSP has abandoned asking for a 3 rd kit on the grounds that the yield was negligible. Methods: We have analysed the outcomes from the 3rd kits returned to the Eastern BCSP Hub from subjects invited for screening between 1 Jan 2011 and 31 March 2012. Results: Over this period over 850, 000 subjects aged 60–74 yrs were invited for screening. 4% (20, 021) completed 3 kits and of these 16% (3192) had a positive 3rdkit and were referred for further investigation. Of those investigated (2830) 4.4% (125) were found to have bowel cancer compared with 17.8% (298) with cancer found after a single kit and 8.1% (483) with cancer found after completing 2 kits. A further 7% and 12% completing 3 kits were found to have high and intermediate risk adenomas. The mean time from selection for screening to obtaining a definitive result for those completing 3 kits was 63 days compared to 34 days for those completing a single kit (95% of all subjects returning kits) and 49 days for those completing 2 kits (1% of all subjects returning kits). Conclusion: A significant number (14%, 125/906) of bowel cancers are detected in those completing 3 kits but this is at the cost of having a screening episode prolonged to almost twice that for subjects obtaining a definitive result after one kit. The intended introduction of faecal immunochemical tests to replace guaiac faecal occult blood tests should allow the use of a simpler and shorter testing algorithm. Disclosure of Interest: None Declared.